ANALISIS TEGANGAN DI POROS ENGKOL YAMAHA RX KING TAHUN 2005 MENGGUNAKAN PERANGKAT LUNAK SOLIDWORK - Emanuel G. N Dhey; Ishak S. Limbong; Matheus M. Dwinanto (Universitas Nusa Cendana, 2023)
The crankshaft is one of the main components that converts the potential energy of the fuel into rotating power for the piston engine. Because in the process of working the crankshaft changes the piston's back and forth motion into a rotating motion of the shaft. To minimize the effects of damage that occurs due to various types of dynamic loads acting on the crankshaft components, the design process should first know the working stress distribution. Meanwhile, as a tool in analyzing it, Solidworks software is used. From the results of this analysis, the location or position of the damage due to too high a loading can be identified early. This the authors in this study want to raise a title, namely